2011
DOI: 10.2147/ijwh.s14188
|View full text |Cite
|
Sign up to set email alerts
|

Trends in serum relaxin concentration among elite collegiate female athletes

Abstract: Purpose:This study was designed to investigate the relationship between serum relaxin concentration (SRC) and menstrual history and hormonal contraceptive use among elite collegiate female athletes. Evaluation of SRC in athletes is necessary, because relaxin has been associated with increased knee joint laxity and decreased anterior cruciate ligament (ACL) strength in animal models.Methods:National Collegiate Athletic Association Division I female athletes participating in sports at high risk for ACL tears – b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
10
0
3
Order By: Relevance
“…In addition, women injure the knee anterior cruciate ligament (ACL) four to six times more often than men, which has prompted the suggestion that fluctuations in women’s endocrine environment might be a factor [ 78 ]. The presence of sex hormones or relaxing receptors in ACL might explain their effect on this structure, but other extrinsic or intrinsic factors may contribute to this process [ 79 , 80 ]. Recent reviews [ 81 , 82 ] seem to show a decreased risk of ACL injury during L vs. F and PeO, with increased ACL laxity in PeO at high E2 levels vs. other MC phases.…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%
“…In addition, women injure the knee anterior cruciate ligament (ACL) four to six times more often than men, which has prompted the suggestion that fluctuations in women’s endocrine environment might be a factor [ 78 ]. The presence of sex hormones or relaxing receptors in ACL might explain their effect on this structure, but other extrinsic or intrinsic factors may contribute to this process [ 79 , 80 ]. Recent reviews [ 81 , 82 ] seem to show a decreased risk of ACL injury during L vs. F and PeO, with increased ACL laxity in PeO at high E2 levels vs. other MC phases.…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%
“…Relaxin treatment in pregnant cattle increased pelvic width and height (Perezgrovas & Anderson, 1982 ; Musah et al., 1986 ), but not in other joints such as wrist and knee ( Weinberg, 1956 ; Marnach et al., 2003 ). Increase in serum relaxin concentration may also correlate with joint laxity ( Lubahn et al., 2006 ; Dragoo et al., 2011a , 2011b ), but this effect during pregnancy is controversial ( Forst et al., 1997 ). Some studies have reported higher relaxin levels in pregnant women with pelvic joint instability or hip joint laxity as compared with controls ( Saugstad, 1991 ; Steinetz et al., 2008 ), while other studies did not ( Ohtera et al., 2002 ).…”
Section: Ligamentmentioning
confidence: 99%
“…While estrogen has been shown to affect ACL laxity in the animal model 43 , little is known with regards to the effect of progesterone and testosterone on knee ligament laxity. Dragoo et al, 57 measured serum relaxin concentration (SRC) in elite collegiate female athletes and had observed a positive correlation between SRC and serum progesterone concentration in athletes who are oligomenorrheic, eumenorrheic, not on oral contraceptive and have ovulatory cycle., In this study, serum progesterone level was measured to confirmed luteal phase measurement of relaxin as relaxin levels are known to be higher in this phase. Other studies involving female athletes have also indicated that knee laxity was increased during ovulation and in the luteal phase of the menstrual cycle 53 .…”
Section: Discussionmentioning
confidence: 99%